Criminal Law and the Adequacy of Environmental Protection – International Legal Standards and Serbia’s Substantive Criminal Legislation – Compatible or Not? - Škulić, Milan (Glasnik Advokatske komore Vojvodine, 2025)
This paper explains the importance of the protection of the environment through criminal law in a legal state characterized by the rule of law. In this context, special attention is paid to the influence of fundamental international legal standards pertaining to environmental protection on the specific normative concept of the protection of the environment through criminal law in Serbia. Emphasizing that the protection of the environment through criminal law has an ultima ratio character, the paper also focuses on defining the basic elements of environmental protection law, both within national legal frameworks and from the standpoint of the impact of relevant international legal sources, in connection with responses through criminal law in this field. International standards in the field of environmental protection, which are applied in the national legal system either through so-called implementation mechanisms or, in certain cases, directly, hold particular importance when assessing the adequacy of the protection of the environment through criminal law. The paper includes an analysis of the principal international standards concerning the environment that are contained in relevant international legal sources, such as certain international treaties/agreements/conventions. It also clarifies the dominant ratio legis of crimes against the environment under the Criminal Code of the Republic of Serbia, with an explanation of the general ratio legis for such crimes, combined with defining the ratio legis of individual crimes classified, according to the statutory systematics, as crimes against the environment. In the conclusion, the paper particularly emphasizes that the immense importance of the protection of the environment through criminal law stems from the crucial significance of a healthy and preserved environment for human health. This importance, based on relevant constitutional provisions, is manifested and advanced through the development of mechanisms for adequate protection of the environment through criminal law. An analysis of the relevant criminal-law norms shows that, from a normative standpoint, the protection of the environment through criminal law in the Republic of Serbia is adequately conceived, whereas certain weaknesses in the application of these specific criminal-law norms exist in practice, especially when it comes to detecting and proving crimes against the environment.